BENARKAH DOSA MENJADI PENYEBAB KESENGSARAAN AYUB? - Sostenis Nggebu (Institut Agama Kristen Negeri Kupang, 2021)
ABSTRAK The purpose of this article is to explain that Job's suffering was not the result of personal sin. Thus the accusations of Job's colleagues about the source of Job's suffering were refuted. The writer takes the descriptive method to discuss this topic in more depth. From this study, the author obtained the fact that the accusations of Job's colleagues about the cause of Job's suffering were based solely on their assumptions, not according to facts. At the end of Job's suffering, God Himself came to Job and reached out to restore Job. Through Job's suffering, God has proven that Satan is a liar because all his tactics to bring Job down were not permitted by God. It seems very clear that the final mouth of his suffering was meant for God to be exalted in Job's life.